(untitled) (Academia Science Repository, 2023)
This article examines the importance of gene polymorphism in the pharmacotherapeutic treatment of allergic diseases. It provides an overview of the current literature on genetic variations affecting the metabolism and effectiveness of medications commonly used in the treatment of allergies, such as antihistamines, corticosteroids and leukotriene modifiers. The article emphasizes the importance of personalized medicine and the possibility of genetic testing for the development of individual treatment plans for patients with allergic diseases.